Evaluating the impact of the 2023-2024 personal income tax reform in Rwanda: An analysis using tax-benefit microsimulation modelling - Antoine de Mahieu; Jesse Lastunen; Jeannette Mukangango; Theogene Harerimana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Establishing an equitable and efficient tax system is essential for reducing poverty, combating inequality, and fostering sustainable economic growth. Rwanda's government has recognized this and implemented significant changes to the personal income tax schedule for 2023 and 2024 as part of broader tax reforms set forth in its Medium-Term Revenue Strategy. This study examines the fiscal and distributional effects of the personal income tax changes, employing a newly-created tax-benefit microsimulation model for Rwanda. Specifically, we compare the reform to a business-as-usual scenario with the previous income tax regime. The analysis shows that the reform enhances the disposable income of many workers, albeit at the expense of reduced government revenue. At the population level, the reform predominantly benefits the highest income deciles, who constitute the majority of income taxpayers in Rwanda. The lowest deciles, for the most part, remain unaffected by the changes.
Keywords: D31; E24; H24; 330; income tax; poverty; inequality; Rwanda; microsimulation